Links between motivation and metacognition and achievement in cognitive performance among primary school pupils - Lara Nieto-Márquez, Natalia; Garcia-Sinausia, Sandra; Pérez Nieto, Miguel Ángel (Anales de Psicología / Annals of Psychology, 2021)
Sundry studies have emphasised the importance of motivation in cognitive performance, as well as its link to metacognitive development. The objective here is to explore the motivation variables that influence the performance of cognitive tasks, along with their effect on metacognition. The study sample consists of 354 primary school pupils aged 8-11 at a state school in the Community of Madrid (Spain). The following measuring in-struments have been used for studying the variables: Motivación para el Aprendizaje y la Ejecución (MAPE-I) [Motivation for Learning and Execu-tion], a questionnaire on motivation variables; the Junior Metacognitive Awareness Inventory (Jr. MAI), for metacognitive variables, and the bat-tery of tests in the Evaluación Neuropsicológica de las Funciones Ejecutivas en Ni-ños (ENFEN) [Neuropsychological Assessment of Executive Functions in Children], for assessing cognitive performance. The results reveal a signifi-cant effect between the motivation for focusing on learning and cognitive performance in the tasks that involve inhibition, flexibility, and working memory. We also find a significant effect between increased effort and knowledge regulation. Furthermore, we analyse the relations between the variables by school year to determine the age effect. We evaluate the re-sults’ academic implications.